Corrosion resistance and metallurgical behaviour of CMT welded Al-LCS dissimilar butt joint exposed in simulated industrial environment. (July 2022) - Selvamani, S.T.; Yoganandan, G.; Bakkiyaraj, M; Sivamaran, V
Cold Metal Transfer welding is a predominant process for joining the Aluminium and Low Carbon Steel (LCS) dissimilar joints with enhanced properties. In addition, these joints have vast application in various simulated industrial environmental conditions. However, the formation of thick intermetallic layers during welding over these joints leads to invoking the corrosion attack and causing a catastrophic failure that is the primary concern in life prediction of the joint. Hence, the corrosion behaviour of AL-LCS dissimilar butt joint exposed in the simulated industrial environment has been studied experimentally and it has been compared with the Cold Metal Transfer (CMT) welded aluminium and LCS similar joints. The potentiodynamic polarization and the electrochemical impedance spectroscopy were carried out in 3.5% aggressive sodium chloride medium with varying benzotriazole corrosion inhibitor with varying the concentrations like 10 ppm, 15 ppm and 20 ppm. The results showed that the corrosion resistance behaviour of CMT welded dissimilar joints are increased with increasing inhibitor concentration. The inhibitor showed effective performance, and the efficiency is also found to be 78–80% at 20ppm, which revealed the enhanced corrosion resistance of dissimilar metal joints in simulated industrial conditions. Finally, the dissimilar joints are characterized by sophisticated analytical techniques.